Linear Epitopes of Paracoccidioides brasiliensis and Other Fungal Agents of Human Systemic Mycoses As Vaccine Candidates - Travassos, Luiz R.; Taborda, Carlos P. (Frontiers in Immunology, 2017)
Dimorphic fungi are agents of systemic mycoses associated with significant morbidity and frequent lethality in the Americas. Among the pathogenic species are Paracoccidiodes brasiliensis and P. lutzii, which predominate in South America; Histoplasma capsulatum, Coccidioides posadasii and C. immitis, and the Sporothrix spp. complex are the most important pathogens. Associated with dimorphic fungi other important infections are caused by yeast such as Candida spp. and Cryptococcus spp. or mold such as Aspergillus spp., which are also fungal agents of deadly infections. Nowadays the actual tendency of therapy is the development of a pan-fungal vaccine. This is, however, not easy because of the complexity of eukaryotic cells and the particularities of different species and isolates. Albeit there are several experimental vaccines being studied, we will focus mainly on peptide vaccines or epitopes of T cell receptors inducing protective fungal responses. These peptides can be carried by antibody inducing β-(1,3)-glucan oligo or polysaccharides, or be mixed with them for administration. The present review discusses the efficacy of linear peptide epitopes in the context of anti-fungal immunization and vaccine proposition.